Pharmacokinetics of paracetamol and its metabolites in women at delivery and post‐partum. (5th February 2013) - Kulo, Aida; Peeters, Mariska Y.; Allegaert, Karel; Smits, Anne; de, Jan; Verbesselt, Rene; Lewi, Liesbeth; van de, Marc; Knibbe, Catherijne A. J.
<x xml:space="preserve">Abstract</x> Aim A recent report on intravenous (i.v.) paracetamol pharmacokinetics (PK) showed a higher total clearance in women at delivery compared with non‐pregnant women. To describe the paracetamol metabolic and elimination routes involved in this increase in clearance, we performed a population PK analysis in women at delivery and post‐partum in which the different pathways were considered. Methods Population PK parameters using non‐linear mixed effect modelling were estimated in a two‐period PK study in women to whom i.v. paracetamol (2 g loading dose followed by 1 g every 6 h up to 24 h) was administered immediately following Caesarean delivery and in a subgroup of the same women to whom single 2 g i.v.loading dose was administered 10–15 weeks post‐partum. Results Population PK analysis was performed based on 255 plasma and 71 urine samples collected in 39 women at delivery and in eight of these 39 women 12 weeks post‐partum. Total clearance was higher in women at delivery compared with 12th post‐partum week (21.1 vs. 11.7 l h−1) due to higher clearances to paracetamol glucuronide (11.6 vs. 4.76 l h−1), to oxidative metabolites (4.95 vs. 2.77 l h−1) and of unchanged paracetamol (1.15 vs. 0.75 l h−1). In contrast, there was no difference in clearance to paracetamol sulphate. Conclusion The increased total paracetamol clearance at delivery is caused by a disproportional increase in glucuronidation clearance and a proportional increase in clearance of unchanged paracetamol and in oxidation clearance, of which the latter may potentially limit further dose increase in this patient group.